2019
DOI: 10.1111/bjd.18035
|View full text |Cite
|
Sign up to set email alerts
|

A narrative review of the definition of ‘flare’ in hidradenitis suppurativa

Abstract: Summary Background Hidradenitis suppurativa (HS) is a chronic, inflammatory condition that can have periodic worsening or flares. Measurement of flare is important because it can inform treatment efficacy; however, it is unclear how HS flare should be defined. Objectives This study reviewed the literature for definitions of HS flare. Methods The PubMed MEDLINE online database was searched on 10 January 2018 and the search was repeated on 8 December 2018 for new publications. Titles and abstracts were screened … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
15
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 41 publications
(93 reference statements)
1
15
1
Order By: Relevance
“…4 Yet a recent literature review demonstrated that there are few precise definitions of HS flare. 5 Notably, it is the person with HS who experiences flare and there is little data pertaining to the lived experience of people with HS to inform flare definition. The aim of this study was to explore the patient perspective of HS flare.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…4 Yet a recent literature review demonstrated that there are few precise definitions of HS flare. 5 Notably, it is the person with HS who experiences flare and there is little data pertaining to the lived experience of people with HS to inform flare definition. The aim of this study was to explore the patient perspective of HS flare.…”
mentioning
confidence: 99%
“…These findings differ from existing definitions, which focus on changes in clinical exam. 5 Thus, there are differences in the lived experience of patients with HS and the definitions in prior studies. The findings of the study should be considered with its limitations.…”
mentioning
confidence: 99%
“…There have been several review articles on cutaneous mucinoses in the literature with suggested classifications. 1,2 Most commonly, cutaneous mucinoses have been classified into primary (metabolic) or secondary (catabolic) processes. 1 Although secondary mucinoses are usually incidental mucin deposits seen on histology only and can be seen in numerous dermatological conditions, 2 occasionally secondary mucin deposition can produce macroscopic deposits of mucin, leading to clinical lesions as has been reported in connective tissue disorders.…”
mentioning
confidence: 99%
“…Kirby et al . 's narrative review in this issue of the BJD is a vital first step in the development of consensus definitions of disease flare, which in turn may lead us to more clinically relevant measures of disease activity. The counting of nodules is highly relevant for mild‐to‐moderate HS in the absence of scarring, tunnel formation and diffuse oedema/lymphoedema.…”
mentioning
confidence: 99%
See 1 more Smart Citation